A project approach to fostering students’ competencies in the professional field "Ecology and environmental management" - Yevgenievna Ryazanova, Natalya; Evgenievna Lobzhanidze, Natalya; Vladimirovna Kazakova, Ekaterina; Michaelovna Avdonina, Alexandra; Igorevich Nikiforov, Andrey (Opción, 2019)
The focus of the paper is a project approach to the formation of students’ competencies necessary for the professional field “Ecology and environmental management”. The paper indicates that the formation of competencies demands to develop students’ scientific basics of rational environmental management and meaningful ideas related to practical skills. Of much importance are certain professional directions and an active life position in the field of protection and improvement of natural environments. Special attention must be paid to rational use and possible increase of natural resour- ces. The research has proved that the competencies under discussion supply the future expert in the field of ecology and environmental management with a profound scientific knowledge about the relationship between nature and society. There is much evidence that the competencies promote tools to help understand the multifaceted significance of nature for society and for everyone. The competencies help to form an understanding that nature is the primary basis of human existence and the place of a human being as a part of nature. The competencies aid to cultivate conscious attention and respect for the natural environment.